2008
DOI: 10.2190/ic.28.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Dream Content in a Representative German Sample: Gender Differences and the Effects of other Socio-Demographic Variables

Abstract: The present study investigated the effects of socio-demographic variables on dream content in a representative sample. The analyses of 380 most recent dreams showed that almost none of the socio-demographic variables like age, gender, marital status, education, income, nor town (or city) of residence size was significantly related to general dream characteristics like dream length, bizarreness, and intensity of dream emotions, thus indicating that dreaming is a universal phenomenon shared by all humans and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…As pointed out in the introduction, there is strong evidence that the gender difference in dream recall is at least partly explained by socialization; similarly, sex role orientation (more femininity/ expressivity and less masculinity/instrumentality) is also related to dream length. Bizarreness was not related to gender or sex role orientation, confirming the finding of Keller (2008-2009) who studied gender differences in dream content in a representative German sample. Regarding dream emotions, male gender and masculinity seem to be associated with more positive and less negative emotions and problems within the dream.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As pointed out in the introduction, there is strong evidence that the gender difference in dream recall is at least partly explained by socialization; similarly, sex role orientation (more femininity/ expressivity and less masculinity/instrumentality) is also related to dream length. Bizarreness was not related to gender or sex role orientation, confirming the finding of Keller (2008-2009) who studied gender differences in dream content in a representative German sample. Regarding dream emotions, male gender and masculinity seem to be associated with more positive and less negative emotions and problems within the dream.…”
Section: Discussionsupporting
confidence: 82%
“…However, one has to keep in mind that most of the earlier studies (e.g., Hall et al, 1982;Hall & Van de Castle, 1966;Schredl, Sahin, & Schäfer, 1998) have included student samples. Keller (2008-2009) have shown that age has an effect on gender differences in dream content, for example, the percentage of male dream characters. Dream length was found not to differ in student samples (Schredl, Sahin, & Schäfer, 1998) but in adolescents (Schredl & Pallmer, 1998): Girls reported longer dreams than boys; a finding parallel to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dream recall frequency can also be increased, especially in low dream recallers, by simple methods like keeping a dream diary (Cohen, 1969;Schredl, 2002). This effect of training is particularly interesting in representative samples because in a recent German study (Schredl & Keller, 2008-09) only 36.8% of the participants were able to report a most recent dream; i.e., in order to increase the representativeness of the dream sample, it might be valuable to apply some kind of "dream recall training. "…”
Section: Discussionmentioning
confidence: 99%
“…The question, however, is whether and how the findings regarding factors that influence dream recall frequency can affect, for example, the ability to report a most recent dream or write down a dream in the diary; this has not been addressed empirically in a systematic way. A recent representative study (Schredl & Keller, 2008-09) found a moderate correlation between a 7-point dream recall frequency scale (Schredl, 2004a) and the report of a most recent dream (r = .487, p < .0001, N = 933), indicating a relatively close relationship between dream recall frequency and the ability to report a most recent dream (taking into account the different measurement levels of the variables: dichotomous vs. 7-point rating scale). The meta-analysis of Schredl and Reinhard (2008) reporting a substantial and robust gender difference in dream recall indicates that the effect size of this gender difference is not affected by the measurement method (questionnaire scales: d = 0.246; dream diaries: d = 0.309; reporting a most recent dream: d = 0.237).…”
Section: )mentioning
confidence: 95%
“…The data collection period of Hall and Van de Castle (1966) ranged from the late 1940s to the early '50s. Subsequent studies in the '70s (Hall et al 1982) and '90s (Schredl et al 2003), and very recent studies (Schredl & Keller 2008 replicated the higher prevalence of physical aggression in men's dreams compared with total aggression. This means that cultural developments such as the women's movement did not affect this sex difference in dreams.…”
Section: Michael Schredlmentioning
confidence: 91%